Delito, represión y percepción de seguridad: la intervención territorial y el conflicto - Fraile, Pedro (Oñati Socio-Legal Series, 2011)
Recent dynamics of globalization and planetary interconnection of the economy and changes in the ways of producing or transformations of the relationship between capital and labour, are notably influencing the morphology of cities and those social and spatial contradictions that emerge from them, as well as strategies of population control and management of the public order that are implemented. Urban landscape or the image that is disseminated of certain zones help to notably form attitudes and behaviours of those who live in the city. Precisely for this reason, critical analysis of certain territorial strategies or of conflict resolution, which is proposed here, is of increasing importance.